Sanksi Hukum Pidana Terhadap Pelaku dan Perlindungan Hukum bagi Korban Investasi Bodong - Marshanda, Saqila Suci Aurel (Proceedings Series on Social Sciences & Humanities, 2024)
The problem that the author wants to look at is what are the criminal sanctions for perpetrators of fraudulent investments and what are the legal protections for victims of fraudulent investments according to Indonesian criminal law. The application of legal sanctions for perpetrators of online investment fraud has not been explicitly regulated in a special law which can provide criminal penalties for perpetrators but is regulated in the Criminal Code Article 372 with a maximum prison sentence of four years or a maximum fine of nine hundred. rupiah, and Article 378 with a maximum prison sentence of 4 years. This research focuses on criminal cases of investment fraud. The main weakness in the legal sector for victims of fraudulent investments is the problem of legal uncertainty. This legal vacuum can result in the effectiveness and optimization of protection for victims of fraudulent investments not being optimal. The fact is that there is still a legal gap that perpetrators of fraudulent investments often escape heavy sanctions. To provide valuable results, the research methodology in this article uses normative juridical analysis, which is one of the methods and techniques of social science analysis. In this regard, normative juridical research is only based on document research using secondary data consisting of statutory regulations, court decisions, legal theory and royalties. The purpose of this research is to provide a discussion regarding the implementation of legal actions in current cases. So, through this research, it can be seen that law according to its function can play a role in resolving several criminal cases in Indonesia, such as the fraudulent investments that the author discusses.